EVALUATION OF PROCESSES OF EROSION IN THE WESTERN PLATEAU OF SAO PAULO: A CASE STUDY AIMING THE SPATIAL INTERACTIONS - Scudeller Zanatta, Felipe Augusto [UNESP]; Lupinacci, Cenira Maria [UNESP]; Boin, Marcos Norberto (Uniao Geomorfologia Brasileira, 2017)
The concern about soil erosion, especially in rural areas, has been increasing in several countries. The thematic is found in researches published in national and international journals, which indicate the significant influence of human action on the temporal scale of denudatory phenomena. Considering it, this article aims to evaluate this problem in the river basin of Areia Dourada, located in the city of Maraba Paulista (SP), through the use of data from various mappings which were systematized in network graphics. We seek to evaluate the influence of physical factors and human action on the triggering and development of erosive forms, considering the area of study as a representative example of erosive problems in Sao Paulo. As a result, the chart scheme made it possible to gauge a large volume of information in a single model, in order to highlight that land use, especially cattle raising, has a significant impact on the development of denudatory processes, which indicates the catalytic character of the human action that generalizes the morphodynamic action. However, the data also show that the erosive forms only reach gullying level where the physical characteristics suggest a greater predisposition to such processes, as the concavities of the slopes. Therefore, the use of the network graphic allowed to evaluate the combinations between the thematic classes in which the erosive process develops with greater intensity, as well as the influence of the human action. It was found that erosive phenomena often occur in sectors whose physical characteristics do not indicate potential for their development, such as the appearance of linear erosive features in top sectors with low relief energy. Such facts are due to the action of land use, especially, in the case studied, of pastures.
Keywords: Erosive Processes; Physical and Anthropic Variables; Network Graphics